Fellow Traveller The Royal Ballet's salute to Balanchine - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The Royal Ballet's salute to Balanchine. Lauren Cuthbertson has a restrained uptown cool that would have made Charles James long to dress her. PALABRAS CLAVE: Georges Balanchine, Royal Ballet, Agon, Prodigal Son.